Efficacy of various Marek's disease vaccines protocols for prevention of Marek's disease virus-induced immunosuppression. Issue 35 (29th July 2016) - Faiz, Nik M.; Cortes, Aneg L.; Guy, James S.; Fogle, Jonathan E.; Gimeno, Isabel M.
Highlights: Protection against tumors is not enough to protect against late-MDV-IS induced by vv+MDV. Currently used vaccine protocols cannot protect against late-MDV-IS induced by vv+MDV. Experimental vaccine Md5ΔMEQ protect against both tumors and late-MDV-IS induced by vv+MDV. Abstract: Marek's disease virus (MDV) induces tumors and severe immunosuppression in chickens. MDV-induced immunosuppression (MDV-IS) is very complex and difficult to study. In particular, the late MDV-IS (late-MDV-IS) is of great concern since it can occur in the absence of lymphoid organ atrophy or gross tumors. We have recently developed a model to reproduce late-MDV-IS under laboratory conditions. This model measures MDV-IS indirectly by assessing the effect of MDV infection on the efficacy of infectious laryngotracheitis (ILT) vaccination; hence the name late-MDV-IS ILT model. In this study, we have used the late-MDV-IS ILT model to evaluate if MD vaccination can protect against late-MDV-IS. One experiment was conducted to determine whether serotype 1 MD vaccines (CVI988 and Md5ΔMEQ) could induce late-MDV-IS by themselves. Three additional experiments were conducted to evaluate efficacy of different MD vaccines (HVT, HVT+SB-1, CVI988, and Md5ΔMEQ) and different vaccine protocols (day-old vaccination, in ovo vaccination, and double vaccination) against late-MDV-IS. Our results show that none of the currently used vaccine protocols (HVT, HVT+SB-1, or CVI988 administered at day of age, in ovo, or in double vaccination protocols) protected against late-MDV-IS induced by vv+MDV strains 648A and 686. Experimental vaccine Md5ΔMEQ administered subcutaneously at one day of age was the only vaccine protocol that significantly reduced late-MDV-IS induced by vv+MDV strain 686. This study demonstrates that currently used vaccine protocols confer high levels of protection against MDV-induced tumors (protection index = 100), but do not protect against late-MDV-IS; thus, commercial poultry flocks could suffer late-MDV-IS even in complete absence of tumors. Our results suggest that MDV-IS might not be related to the development of tumors and novel control methods are needed. Further evaluation of the experimental vaccine Md5ΔMEQ might shed light on protective mechanisms against late-MDV-IS.